ANALYSIS OF THE INFLUENCE OF SYSTEM AND SERVICE QUALITY ON USER SATISFACTION OF THE YOGYAKARTA ELECTRONIC PROCUREMENT SYSTEM - Drajad Aprilianto Nugroho; Linawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study analyzes the effect of system quality and service quality on user satisfaction of the Electronic Procurement System (SPSE) in the Yogyakarta Special Region Regional Government environment with a quantitative descriptive approach through multiple linear regression methods. Background: The Electronic Procurement System (SPSE) designed by LKPP, namely to improve the effectiveness and efficiency of procurement of goods and services and save APBN/APBD funds. In addition, it is also stated that the quality of information systems and services greatly influences SPSE user satisfaction. Method: this study uses a quantitative descriptive method with primary data from questionnaires, as well as multiple regression analysis. This explains the approach used in the study to collect and analyze data. Results: the results of the study indicate that system quality and service quality both have a positive and significant effect on SPSE user satisfaction. This provides information about the main findings of the study. Conclusion: the positive and significant effect of system quality and service quality has an impact on the effectiveness and efficiency of the procurement process. This summarizes the implications of the research results and emphasizes the importance of both variables in the context of procurement of goods and services.